The dominant control of wind-driven asymmetry and sediment export on carbonate slope around a semi-enclosed atoll in the South China Sea - Liu, Gang; Chen, Wanli; Wu, Shiguo; Chen, Junjin; Sun, Yue; Zeng, Fanchang; Li, Xuelin (Frontiers in Marine Science, 2025)
Carbonate slopes and their associated relocated deposits are of significant interest due to their potential as hydrocarbon reservoir. This study investigates the geomorphology and depositional processes of carbonate slopes in the semi-enclosed Xuande Atoll, South China Sea, using high-resolution acoustic data, seismic profiles, and topographic analysis. Our results reveal that the modern morphology of the carbon slope is shaped by depositional and erosive processes that differ markedly between the windward (northeastern) and leeward (southwestern) slopes. The wind-related asymmetric facies distribution on the platform top drives distinct slope geomorphologies. On the windward slope, mass-transport complexes (MTCs) exhibit limited transport distances or remnant deposits, likely due to the influence of coarse and heavy sediments sourced from reef flats, transported as calcidebrites. Additionally, drift sedimentation on the windward slope indicates the impact of contour currents. In contrast, the leeward slope is characterized by gullies and channels, suggesting that fine and light carbonate sediments from the interior platform were transported by wind-driven currents as calciturbidites, cutting the slope. Most MTCs on the leeward slope exhibit long-distance transportation, closely associated with the input of fine and light carbonate sediments from the interior platform. We demonstrate that wind-related asymmetric facies distribution and sediment export are key factors contributing to the pronounced contrast in the windward and leeward slope geomorphologies of Xuande Atoll. The combination of processes results in spatially heterogeneous sedimentation on both the top and slope of the platform, which has significant implications for understanding reservoir heterogeneity and predicting hydrocarbon distribution in ancient carbonate platforms.